Cogeneration system design optimization - Balestieri, José Antônio Perrella [UNESP]; Correia, Paulo de Barros (My University, 1996)
Cogeneration system design deals with several parameters in the synthesis phase, where not only a thermal cycle must be indicated but the general arrangement, type, capacity and number of machines need to be defined. This problem is not trivial because many parameters are considered as goals in the project. An optimization technique that considers costs and revenues, reliability, pollutant emissions and exergetic efficiency as goals to be reached in the synthesis phase of a cogeneration system design process is presented. A discussion of appropriated values and the results for a pulp and paper plant integration to a cogeneration system are shown in order to illustrate the proposed methodology.
Keywords: Cogeneration; Design; Efficient Solutions; Multiple Programming; Optimization